Gangue heavy metal curing agent and preparation method and use method thereof

By using gangue heavy metal curing agent composed of sodium-based bentonite, bentonite activator, fly ash and sodium polyacrylate solution, a chelating point and gelling network structure are formed, which solves the problem of insufficient adsorption and curing effects of gangue heavy metal curing agent in the prior art, and achieves efficient heavy metal curing and solid distribution uniformity.

CN116283054BActive Publication Date: 2025-04-29SHENHUA SHENDONG COAL GRP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310322372.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-04-29
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

The adsorption and curing effect of existing gangue heavy metal curing agents is insufficient, and they are easy to decompose, which cannot effectively prevent the dissolution and migration of heavy metals, resulting in soil and water pollution.

Method used

The gangue heavy metal curing agent including material A and material B is used. Material A is composed of sodium-based bentonite, bentonite activator, fly ash and water. Material B is a sodium polyacrylate solution. The chelating point and gelation network structure are formed through the bentonite activator to enhance the cross-linking and curing effect.

Benefits of technology

Strong adsorption and fixation of heavy metal ions such as cadmium, lead, chromium, and mercury are achieved, and layering is avoided by geological settlement or rainwater erosion, maintain uniform heavy metal curing distribution, and improve the environmental protection and safety of the curing agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004152273020000091
    Figure BDA0004152273020000091
  • Figure BDA0004152273020000101
    Figure BDA0004152273020000101
  • Figure BDA0004152273020000102
    Figure BDA0004152273020000102
Patent Text Reader

Abstract

The present invention provides a gangue heavy metal curing agent and a preparation method and a use method thereof. The gangue heavy metal curing agent comprises material A and material B, and the mass ratio of the two is 100:40-100. In terms of mass fractions, material A comprises 3-5 parts of sodium-based bentonite, 0.003-0.03 parts of bentonite activator, 30-50 parts of fly ash, and 100 parts of water; material B is a sodium polyacrylate solution with a solid content of 30-40wt%, and the weight-average molecular weight of sodium polyacrylate is 1200-20000, and the molecular weight distribution coefficient is 1.7-2.5. The gangue heavy metal curing agent provided by the present application forms chelating sites on the inner and outer surfaces of sodium-based bentonite through the bentonite activator, has a strong adsorption effect on heavy metal ions, and combines sodium-based bentonite and fly ash, which can not only maintain high adsorption activity, but also facilitate the adsorption and fixation of heavy metal ions, and at the same time can avoid stratification caused by geological settlement or rainwater erosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental governance, and in particular to a gangue heavy metal solidifying agent and a preparation method and a use method thereof. Background Art

[0002] The development of coal resources will bring a large amount of solid waste such as gangue and fly ash. At present, the cumulative amount of gangue in my country exceeds 6 billion tons, which has jumped to the top of the national industrial waste, and is increasing year by year at an annual emission of about 500 to 800 million tons. Gangue mountains are formed by the accumulation of such solid waste. With the expansion of my country's economic development and the continuous growth of energy demand, thousands of gangue mountains of different sizes have been formed, and they will continue to grow. The coal-based solid wastes such as coal gangue discharged during coal mining, washing and processing, and power generation contain trace amounts of harmful heavy metals, such as cadmium, lead, chromium, and mercury. These harmful heavy metals will penetrate into the soil in and around the gangue mountain with rainwater and coal gangue washing and discharge water, causing pollution to the soil, surface water and groundwater. In addition, it also causes the withering of trees near the mining area, the reduction of crop yields, and the serious damage to the ecological environment. Based on this, it is necessary to solidify the heavy metals in the gangue to prevent them from dissolving and migrating from the gangue.

[0003] In the prior art, one approach is to use microorganisms to solidify heavy metals in coal gangue. The microorganism attachment treatment is performed before the gangue is filled, and the heavy metals in the gangue in the goaf are directly solidified. However, this method requires first detecting the heavy metal ion content of the gangue to be filled, and selecting the bacterial strain based on the measurement results. In actual applications, different bacterial strains need to be cultivated, which is costly. Another idea is to form a crosslink or seal with the gangue. In the prior art, there is a heavy metal solidifier for gangue that is achieved by preparing a composite activator formed by water glass and potassium hydroxide. This method has a simple process and a strong adsorption capacity for heavy metals. However, under the complex external ecological environment, the "crystal-like" structure formed is prone to decomposition, so the solidification effect is general.

[0004] In addition, since a large amount of coal gangue in the gangue is a mixture of carbonaceous, muddy and sandy shale, it has a low calorific value and is prone to spontaneous combustion. Therefore, there is an urgent need for a heavy metal solidifier with simple process and excellent adsorption and solidification effects. Summary of the invention

[0005] The main purpose of the present invention is to provide a gangue heavy metal solidifying agent and a preparation method and a use method thereof, so as to solve the problem that the gangue heavy metal solidifying agent in the prior art has insufficient effect in adsorbing and solidifying heavy metals and is easy to decompose.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a gangue heavy metal solidifier is provided, which includes material A and material B, and the mass ratio of material A to material B is 100:40-100, wherein material A includes 3-5 parts of nano-bentonite, 0.003-0.03 parts of bentonite activator, 30-50 parts of fly ash, and 100 parts of water, by mass; material B is a sodium polyacrylate solution with a solid content of 30-40wt%, and the weight average molecular weight of the sodium polyacrylate is 1200-20000, and the molecular weight distribution coefficient is 1.7-2.5.

[0007] Furthermore, the mass ratio of material A to material B is 100:60-80.

[0008] Furthermore, the gangue heavy metal solidifying agent also includes calcium oxide, and the mass of the calcium oxide is 2-5% of the total mass of the solid dry basis in the gangue heavy metal solidifying agent.

[0009] Furthermore, the gangue heavy metal curing agent also includes a pH regulator, which is used to adjust the pH of the gangue heavy metal curing agent, and the pH of the gangue heavy metal curing agent is 6.5-8.

[0010] Furthermore, the bentonite activator is selected from rare earth element oxalates or carbonates, and the rare earth element is selected from at least one of lanthanum, cerium, yttrium or dysprosium.

[0011] Furthermore, the raw materials of the sodium polyacrylate solution include acrylic acid monomer, initiator, isopropyl alcohol, organic solubilizer, water and sodium hydroxide solution.

[0012] Furthermore, the organic solubilizer is selected from at least one of n-butanol, ethyl acetate or ethyl propyl ether; the initiator is selected from at least one of ammonium sulfate or potassium persulfate; and the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30-40%.

[0013] Furthermore, material B is prepared according to the following steps: first, isopropanol, an organic solubilizer and water are mixed evenly, then an initiator and an acrylic acid monomer are added and mixed evenly, and a polymerization reaction is carried out to obtain a polyacrylic acid solution, and then sodium hydroxide is added to the polyacrylic acid solution, and the mixture is allowed to stand to obtain a sodium polyacrylate solution.

[0014] Furthermore, the polymerization reaction temperature is 70-80° C., and the time is 1-4 hours.

[0015] According to another aspect of the present application, a method for preparing a gangue heavy metal solidifier is also provided, the preparation method comprising: step S1, mixing sodium bentonite, bentonite activator, fly ash and water to obtain material A; step S2, mixing material A and material B to obtain the gangue heavy metal solidifier.

[0016] According to the third aspect of the present application, a method for using a gangue heavy metal solidifier is also provided, the method comprising: mixing gangue particles with any one of the gangue heavy metal solidifiers provided in the first aspect and oxidizing the mixture for 6 to 8 days; wherein the mass ratio of the gangue particles to the solid dry basis in the gangue heavy metal solidifier is (60 to 95):(40 to 5), preferably (70 to 85):(30 to 15).

[0017] Furthermore, the D50 of the gangue particles is 50-200 meshes.

[0018] Furthermore, the gangue particles are formed by crushing the gangue, and preferably the gangue is sintered at a high temperature, wherein the temperature of the high temperature sintering is 600-900°C.

[0019] Applying the technical solution of the present application, the gangue heavy metal curing agent provided by the present application forms chelating sites on the inner and outer surfaces of sodium bentonite through a bentonite activator, and has a strong adsorption effect on heavy metal ions such as cadmium, lead, chromium, and mercury. The bentonite is porous inside, and fly ash exists in the form of a filling carrier. The sodium bentonite and fly ash are matched, which can not only maintain high adsorption activity, but also facilitate the adsorption and fixation of heavy metal ions. At the same time, it will not be stratified due to geological settlement or rain erosion, and a uniform distribution of heavy metal curing is always maintained. In addition, the present application further enhances the cross-linking curing effect by compounding material A with a sodium polyacrylate solution to form a gelled network structure, and uses heavy metal ions to participate in a water chemical reaction and be sealed in a cured network structure formed by sodium polyacrylate. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] As analyzed in the background technology of this application, the existing gangue heavy metal solidifier has the problem of insufficient adsorption and solidification of heavy metals and easy decomposition. In order to solve this problem, this application provides a gangue heavy metal solidifier and its preparation method and use method.

[0022] In a first typical embodiment of the present application, a gangue heavy metal solidifier is provided, which includes material A and material B, and the mass ratio of material A to material B is 100:40-100, wherein material A includes 3-5 parts of sodium bentonite, 0.003-0.03 parts of bentonite activator, 30-50 parts of fly ash, and 100 parts of water, by mass; material B is a sodium polyacrylate solution with a mass solid content of 30-40%, and the weight average molecular weight of the sodium polyacrylate is 1200-20000, and the molecular weight distribution coefficient is 1.7-2.5.

[0023] In the gangue heavy metal curing agent provided in the present application, the mass ratio of material A to material B includes but is not limited to 100:40, 100:50, 100:60, 100:70, 100:80, 100:90, 100:100 or a range value consisting of any two numerical values.

[0024] The gangue heavy metal curing agent provided in the present application forms chelating sites on the inner and outer surfaces of sodium bentonite through a bentonite activator, and has a strong adsorption effect on heavy metal ions such as cadmium, lead, chromium, and mercury. The bentonite is porous inside, and fly ash exists in the form of a filling carrier. The sodium bentonite and fly ash are matched, which can not only maintain high adsorption activity, but also facilitate the adsorption and fixation of heavy metal ions. At the same time, it will not be stratified due to geological settlement or rain erosion, and a uniform distribution of heavy metal curing is always maintained. In addition, the present application further enhances the cross-linking curing effect by compounding material A with a sodium polyacrylate solution to form a gelled network structure, and uses heavy metal ions to participate in a water chemical reaction and be sealed in a cured network structure formed by sodium polyacrylate.

[0025] [A material]

[0026] In the present application, material A includes sodium bentonite, bentonite activator, fly ash and water. Taking the mass of water as 100 parts, the mass fraction of sodium bentonite is 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or a range consisting of any two numerical values; the bentonite activator is 0.003 parts, 0.005 parts, 0.01 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.03 parts or a range consisting of any two numerical values; the fly ash is 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts or a range consisting of any two numerical values.

[0027] The bentonite activator is used to activate bentonite, improve the polarity of bentonite, and then improve the adsorption performance and chelating performance of bentonite. The type of the bentonite activator is not specifically limited, especially when the bentonite activator is selected from rare earth element oxalate or carbonate, it is more conducive to further improving the activation performance of bentonite. The rare earth element includes but is not limited to any one of lanthanum, cerium, yttrium or dysprosium.

[0028] The fly ash is the fine ash collected from the flue gas after coal combustion, and is the main solid waste discharged from coal-fired power plants. The fly ash is combined with sodium bentonite and bentonite activator, and the fly ash exists in the form of a filling carrier, which makes full use of the solid waste materials from coal mining, and can not only further improve the adsorption and fixation performance of the gangue heavy metal solidifier for heavy metal ions, but also make the gangue heavy metal solidifier have a more excellent soil and water conservation effect.

[0029] [B material]

[0030] The material B is a sodium polyacrylate solution with a solid content of 30-40wt%, and the weight average molecular weight of the sodium polyacrylate is 1000-20000, and the molecular weight distribution coefficient is 1.7-2.5, so as to form a gel network with the material A, further enhance the cross-linking and curing effect, and utilize heavy metal ions to participate in the water chemical reaction and be enclosed in the curing material formed by the sodium polyacrylate. The weight average molecular weight of the polyacrylic acid is 1200, 1500, 2000, 5000, 8000, 1000, 12000, 15000, 18000, 20000 or a range value composed of any two values; the molecular weight distribution coefficient is 1.7, 1.8, 2.0, 2.2, 2.5 or a range value composed of any two values.

[0031] The raw materials of the sodium polyacrylate solution are not specifically limited. From the perspective of improving preparation efficiency and reducing costs, the raw materials of the sodium polyacrylate solution include acrylic acid monomer, initiator, isopropanol, organic solubilizer, water and sodium hydroxide solution. Among them, the organic solubilizer is used to promote the dispersion and dissolution of each raw material, which includes but is not limited to a mixed organic solvent formed by any one or more of n-butanol, butyl acetate or isopropyl ether. The initiator includes but is not limited to a mixed initiator formed by any one or two of ammonium sulfate or potassium persulfate. From the perspective of facilitating ion exchange, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30-40%.

[0032] The preparation method of the material B is not specifically limited. In some embodiments of the present application, the material B is prepared according to the following steps: isopropyl alcohol, an organic solubilizer and water are mixed evenly, an initiator and an acrylic acid monomer are added and mixed evenly, and a polymerization reaction is carried out to obtain a polyacrylic acid solution, and then sodium hydroxide is added to the polyacrylic acid solution, and the mixture is allowed to stand to obtain a sodium polyacrylate solution.

[0033] From the perspective of improving the efficiency of the polymerization reaction, the preferred polymerization reaction temperature is 70-80°C (such as 70°C, 72°C, 75°C, 78°C, 80°C or a range consisting of any two numerical values), and the time is 1-4h (such as 1h, 1.5h, 2h, 3h, 4h or a range consisting of any two numerical values).

[0034] From the perspective of improving preparation efficiency, the standing time is preferably 8 to 20 min, such as 8 min, 10 min, 12 min, 15 min, 18 min, 20 min or a range consisting of any two values.

[0035] The above-mentioned material A and material B cooperate with each other to improve the adsorption and fixation performance of the gangue heavy metal solidifying agent, especially when the mass ratio of material A to material B is 100:60-80, the formed gangue heavy metal solidifying agent has more excellent adsorption and fixation performance.

[0036] In order to further improve the heavy metal ion adsorption and fixation ability of the gangue heavy metal curing agent, it is preferred that the gangue heavy metal curing agent also includes calcium oxide to further improve the fixation ability of heavy metal ions. Based on the total mass of the solid in the gangue heavy metal curing agent, the mass of the calcium oxide is 2-5% of the total mass of the gangue heavy metal curing agent solid dry basis, including but not limited to 2%, 3%, 4%, 5% or a range of any two numerical values. In particular, when the mass of calcium oxide is 3-4.5% of the total mass of the gangue heavy metal curing agent solid dry basis, it is more conducive to improving the adsorption and fixation ability of the gangue heavy metal curing agent.

[0037] In order to further improve the environmental safety of the gangue heavy metal curing agent, the gangue heavy metal curing agent preferably also includes a pH regulator, which is used to adjust the pH of the gangue heavy metal curing agent to 6.5-8, thereby further improving its environmental safety.

[0038] In a second typical embodiment of the present application, a preparation method of the above-mentioned gangue heavy metal curing agent is also provided, and the preparation method comprises: step S1, mixing sodium bentonite, bentonite activator, fly ash and water to obtain material A; step S2, mixing material A and material B to obtain the gangue heavy metal curing agent. The preparation method has a simple process, and the preparation of the gangue heavy metal curing agent can be achieved by mixing. It is easy to operate, does not require complex processes and control methods, and is more conducive to large-scale production, thereby further reducing the preparation cost of the gangue heavy metal curing agent.

[0039] When the gangue heavy metal solidifying agent contains calcium oxide, during its preparation, in step S2, material A, material B and calcium oxide are uniformly mixed.

[0040] When the gangue heavy metal curing agent contains a pH adjuster, during its preparation, in step S2, material A, material B and the pH adjuster are evenly mixed, and the pH of the gangue heavy metal curing agent is adjusted to 6.5-8 by the pH adjuster.

[0041] In a third typical embodiment of the present application, a method for using the above-mentioned gangue heavy metal solidifier is also provided, and the method for using includes: mixing the gangue particles with the gangue heavy metal solidifier and curing for 6 to 8 days to complete the adsorption and solidification treatment of the heavy metal ions in the gangue particles, wherein the mass ratio of the solid dry basis of the gangue particles and the gangue heavy metal solidifier is (60 to 95): (40 to 5), such as 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5 or a range value composed of any two numerical values.

[0042] In order to prevent the gangue heavy metal curing agent from being difficult to mix evenly with the gangue particles after curing, it is preferred to mix material A and material B to form the gangue heavy metal curing agent 10 to 30 minutes before mixing with the gangue particles.

[0043] In order to further improve the heavy metal curing effect, the preferred curing conditions are: curing at room temperature and relative humidity of 90% for 6 to 8 days.

[0044] In order to facilitate uniform mixing of the above-mentioned gangue heavy metal curing agent and gangue particles, the particle size of the gangue particles is preferably 50-200 mesh, and more preferably 80-120 mesh, such as 50 mesh, 80 mesh, 100 mesh, 120 mesh, 150 mesh, 180 mesh, 200 mesh or a range consisting of any two values.

[0045] In view of the high carbon content in gangue and the risk of flammability, in order to further reduce the flammability of gangue particles, it is preferred to subject the gangue to high-temperature sintering treatment to reduce the carbon content in the gangue and then crush it into gangue particles of corresponding particle size and mix it with the gangue heavy metal solidifier.

[0046] From the perspective of improving high-temperature sintering efficiency and reducing carbon content, the preferred high-temperature sintering temperature is 600-900°C, such as 600°C, 700°C, 800°C, 900°C or a range consisting of any two values.

[0047] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0048] Example 1

[0049] The present embodiment provides a gangue heavy metal curing agent, including 100kg A material, 70kg B material, 1.7kg calcium oxide and a pH regulator, wherein the A material is a mixture of 4kg sodium bentonite, 0.02kg cerium oxalate, 40kg fly ash and 100kg water; the B material is a sodium polyacrylate solution, and the solid content of the solution is 40wt%, the weight average molecular weight of the sodium polyacrylate is 12000, and the molecular weight distribution coefficient is 2.1; the pH regulator is used to adjust the pH value of the gangue heavy metal curing agent to 7.1.

[0050] The sodium polyacrylate solution is prepared according to the following steps: 15 kg of isopropanol, 60 kg of n-butanol and 15 kg of water are mixed, 0.1 kg of ammonium persulfate and 10 kg of acrylic acid monomer are added dropwise, the mixture is kept warm at 75° C. for 2 hours, and then a sodium hydroxide solution with a mass concentration of 40% is added, and the mixture is allowed to stand for 10 minutes to obtain a sodium polyacrylate solution.

[0051] The gangue heavy metal curing agent is prepared according to the following steps:

[0052] (1) sodium bentonite, cerium oxalate, fly ash and water were mixed and stirred for 20 minutes to form chelating sites on the inner and outer surfaces of the sodium bentonite to obtain material A;

[0053] (2) 100 kg of material A, 70 kg of material B and 1.7 kg of calcium oxide were mixed evenly, and a pH adjuster was added to adjust the pH of the mixed solution to 7.1 to obtain a gangue heavy metal solidifying agent.

[0054] Example 2

[0055] The present embodiment provides a gangue heavy metal solidifying agent, which includes 100kg A material, 70kg B material, 2.8kg calcium oxide and a pH regulator, wherein the A material is a mixture of 5kg sodium bentonite, 0.03kg cerium oxalate, 50kg fly ash and 100kg water; the B material is a sodium polyacrylate solution, and the solid content of the solution is 40wt%, the weight average molecular weight of the sodium polyacrylate is 15000, and the molecular weight distribution coefficient is 1.8; the pH regulator is used to adjust the pH of the gangue heavy metal solidifying agent to 7.5, and is specifically sodium carbonate.

[0056] The sodium polyacrylate solution is prepared according to the following steps: 20 kg of isopropanol, 55 kg of n-butanol and 15 kg of water are mixed, 0.08 kg of ammonium persulfate and 10 kg of acrylic acid monomer are added dropwise, the mixture is kept warm at 75° C. for 2 hours, and then a sodium hydroxide solution with a mass concentration of 40% is added, and the mixture is allowed to stand for 10 minutes to obtain a sodium polyacrylate solution.

[0057] The following steps are used to prepare:

[0058] (1) mixing sodium bentonite, cerium oxalate, fly ash and water for 20 minutes to form chelating sites on the inner and outer surfaces of the sodium bentonite to obtain material A;

[0059] (2) 100 kg of material A, 70 kg of material B and 2.8 kg of calcium oxide were mixed evenly, and a pH adjuster was added to adjust the pH of the mixed solution to 7.5 to obtain a gangue heavy metal solidifying agent.

[0060] Example 3

[0061] The present embodiment provides a gangue heavy metal solidifying agent, which includes 100kg A material, 40kg B material, 1kg calcium oxide and a pH regulator, wherein the A material is a mixture of 3kg sodium bentonite, 0.003kg cerium oxalate, 30kg fly ash and 100kg water; the B material is a sodium polyacrylate solution, and the solid content of the solution is 30wt%, the weight average molecular weight of the sodium polyacrylate is 1200, and the molecular weight distribution coefficient is 1.7; the pH regulator is used to adjust the pH of the gangue heavy metal solidifying agent to 7.8, and is specifically sodium carbonate.

[0062] The sodium polyacrylate solution is prepared according to the following steps: 10 kg of isopropanol, 35 kg of n-butanol and 45 kg of water are mixed, 1.2 kg of ammonium persulfate and 10 kg of acrylic acid monomer are added dropwise, the mixture is kept warm at 85° C. for 1 hour, and then a sodium hydroxide solution with a mass concentration of 40% is added, and the mixture is allowed to stand for 10 minutes to obtain a sodium polyacrylate solution.

[0063] The gangue heavy metal curing agent is prepared by the following steps:

[0064] (1) mixing sodium bentonite, cerium oxalate, fly ash and water for 20 minutes to form chelating sites on the inner and outer surfaces of the sodium bentonite to obtain material A;

[0065] (2) 100 kg of material A, 40 kg of material B and 1 kg of calcium oxide were mixed evenly, and a pH adjuster was added to adjust the pH of the mixed solution to 7.8 to obtain a gangue heavy metal solidifying agent.

[0066] Example 4

[0067] The present embodiment provides a gangue heavy metal curing agent, which includes 100kg A material, 70kg B material and a pH regulator, wherein the A material is a mixture of 4kg sodium bentonite, 0.02kg yttrium carbonate, 40kg fly ash and 100kg water; the B material is a sodium polyacrylate solution, and the solid content of the solution is 40wt%, the weight average molecular weight of the sodium polyacrylate is 12000, and the molecular weight distribution coefficient is 2.1; the pH regulator is used to adjust the pH of the gangue heavy metal curing agent to 6.5, and is specifically citric acid.

[0068] The sodium polyacrylate solution is prepared according to the following steps: 15 kg of isopropanol, 60 kg of n-butanol and 15 kg of water are mixed, 0.1 kg of ammonium persulfate and 10 kg of acrylic acid monomer are added dropwise, the mixture is kept warm at 75° C. for 2 hours, and then a sodium hydroxide solution with a mass concentration of 40% is added, and the mixture is allowed to stand for 10 minutes to obtain a sodium polyacrylate solution.

[0069] The gangue heavy metal curing agent is prepared by the following steps:

[0070] (1) mixing sodium bentonite, cerium oxalate, fly ash and water for 20 minutes to form chelating sites on the inner and outer surfaces of the sodium bentonite to obtain material A;

[0071] (2) 100 kg of material A and 70 kg of material B were mixed evenly, and a pH adjuster was added to adjust the pH of the mixed solution to 6.5 to obtain a gangue heavy metal solidifying agent.

[0072] Example 5

[0073] The difference between this embodiment and embodiment 1 is that the amount of material B used is 60 kg.

[0074] Example 6

[0075] The difference between this embodiment and embodiment 1 is that the amount of material B used is 80 kg.

[0076] Example 7

[0077] The difference between this embodiment and embodiment 1 is that the amount of material B used is 100 kg.

[0078] Example 8

[0079] The difference between this embodiment and embodiment 1 is that material B is a sodium polyacrylate solution, and the solid content of the solution is 40 wt %, the weight average molecular weight of the sodium polyacrylate is 20,000, and the molecular weight distribution coefficient is 2.5.

[0080] Example 9

[0081] The difference between this embodiment and embodiment 1 is that lanthanum oxalate is used to replace cerium oxalate.

[0082] Example 10

[0083] The difference between this embodiment and embodiment 1 is that cerium oxalate is replaced by dysprosium carbonate.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that no cerium oxalate is added to material A.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 1 is that the gangue heavy metal solidifying agent does not contain material B, and is a mixture of 100 kg material A and 1.7 kg calcium oxide, and a pH regulator is added to adjust the pH to 7.1.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is that the gangue heavy metal solidifying agent does not contain material A, and is mixed with 100 kg of material B and 1.7 kg of calcium oxide, and a pH regulator is added to adjust the pH to 7.1.

[0090] Comparative Example 4

[0091] The difference between this comparative example and Example 1 is that the amount of material B used is 30 kg.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 1 is that the amount of material B used is 120 kg.

[0094] Comparative Example 6

[0095] The difference between this comparative example and Example 1 is that the weight average molecular weight of the sodium polyacrylate in material B is 1000.

[0096] Comparative Example 7

[0097] The difference between this comparative example and Example 1 is that in material B, the weight average molecular weight of sodium polyacrylate is 10,000, and the molecular weight distribution coefficient is 3.

[0098] Comparative Example 8

[0099] The difference between this comparative example and Example 1 is that in material B, the weight average molecular weight of the sodium polyacrylate is 25,000.

[0100] Comparative Example 9

[0101] The difference between this comparative example and Example 1 is that in material A, the amount of fly ash used is 20 kg.

[0102] Comparative Example 10

[0103] The difference between this comparative example and Example 1 is that no fly ash is added to material A.

[0104] Test Example 1

[0105] The gangue heavy metal solidifying agents provided in the above embodiments and comparative examples were used to solidify gangue particles, and leaching experiments were carried out according to HJ557-2009 "Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid and Nitric Acid Method" to detect the dissolution amount of heavy metals in the solidified samples. The results are shown in Table 1 below.

[0106] The above-mentioned method for solidifying gangue particles is specifically carried out according to the following steps:

[0107] (1) The gangue is sintered at 700°C for 3 hours, and then the sintered gangue is crushed and ground in sequence to obtain gangue particles with a particle size range of 80 to 120 meshes.

[0108] (2) Within 30 minutes after the gangue heavy metal curing agent provided in the above embodiments and comparative examples is prepared, the gangue heavy metal curing agent is mixed evenly with the gangue particles to obtain a mixture of gangue particles and curing agent, and the amount of gangue particles used is 90 kg, and the total mass of the gangue heavy metal curing agent solid dry basis is 10 kg.

[0109] (3) Oxidation was performed at room temperature and relative humidity of 90% for 7 days to form a cured sample.

[0110] Table 1

[0111]

[0112]

[0113] Test Example 2

[0114] The gangue heavy metal solidifying agent (solid dry basis mass) provided in Example 1 was used to solidify the gangue particles according to the mass ratio in Table 2. The solidification method was the same as that in Experimental Example 1. The leaching experiment was carried out according to HJ557-2009 "Toxicity leaching method for solid waste leaching-sulfuric acid and nitric acid method" to detect the dissolution amount of heavy metals in the solidified samples. The results are shown in Table 2 below.

[0115] Table 2

[0116]

[0117] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the gangue heavy metal curing agent provided by the application forms chelating sites on the inner and outer surfaces of sodium bentonite through the bentonite activator, and has a strong adsorption effect on heavy metal ions such as cadmium, lead, chromium, and mercury. The bentonite is porous inside, and fly ash exists in the form of a filling carrier. The sodium bentonite and fly ash are matched, which can not only maintain high adsorption activity, but also facilitate the adsorption and fixation of heavy metal ions. At the same time, it will not be stratified due to geological settlement or rainwater erosion, and always maintain a uniform distribution of heavy metal curing. In addition, the present application further enhances the cross-linking curing effect by compounding material A with sodium polyacrylate solution to form a gelled network structure, and uses heavy metal ions to participate in water chemical reactions and be sealed in the cured network structure formed by sodium polyacrylate.

[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A gangue heavy metal curing agent, characterized in that: The gangue heavy metal curing agent includes material A and material B, and the mass ratio of material A to material B is 100:40-80, wherein the material A includes 3-5 parts of sodium bentonite, 0.003-0.03 parts of bentonite activator, 30-50 parts of fly ash, and 100 parts of water in parts by mass; the material B is a sodium polyacrylate solution with a solid content of 30-40wt%, and the weight average molecular weight of the sodium polyacrylate is 1200-20000, and the molecular weight distribution coefficient is 1.7-2.5; the gangue heavy metal curing agent also includes calcium oxide, and the mass of the calcium oxide is 2-5% of the total mass of the solid dry basis in the gangue heavy metal curing agent; the bentonite activator is selected from rare earth element oxalate or carbonate, and the rare earth element is selected from at least one of lanthanum, cerium, yttrium or dysprosium.

2. The gangue heavy metal curing agent according to claim 1, characterized in that: The mass ratio of the A material to the B material is 100:60-80.

3. The gangue heavy metal curing agent according to claim 1, characterized in that: The gangue heavy metal curing agent further comprises a pH adjusting agent, and the pH adjusting agent is used to adjust the pH of the gangue heavy metal curing agent, and the pH of the gangue heavy metal curing agent is 6.5-8.

4. The gangue heavy metal solidifying agent according to any one of claims 1 to 3, characterized in that: The raw materials of the sodium polyacrylate solution include acrylic acid monomer, initiator, isopropanol, organic solubilizer, water and sodium hydroxide solution.

5. The gangue heavy metal curing agent according to claim 4, characterized in that: The organic solubilizer is selected from at least one of n-butanol, butyl acetate or ethyl propyl ether; the initiator is selected from at least one of ammonium sulfate or potassium persulfate; and the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 30-40%.

6. The gangue heavy metal curing agent according to claim 4, characterized in that: The material B is prepared according to the following steps: first, the isopropanol, the organic solubilizer and the water are uniformly mixed, then the initiator and the acrylic acid monomer are added and mixed uniformly, and a polymerization reaction is carried out to obtain a polyacrylic acid solution, and then sodium hydroxide is added to the polyacrylic acid solution, and the mixture is allowed to stand to obtain the sodium polyacrylate solution.

7. The gangue heavy metal curing agent according to claim 6, characterized in that: The polymerization reaction temperature is 70-80° C. and the reaction time is 1-4 hours.

8. A method for preparing a gangue heavy metal curing agent according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Step S1, mixing the sodium bentonite, the bentonite activator, the fly ash and the water to obtain the material A; Step S2, mixing the material A and the material B to obtain a gangue heavy metal curing agent.

9. A method for using the gangue heavy metal curing agent according to any one of claims 1 to 7, characterized in that: The method of use comprises: mixing gangue particles with the gangue heavy metal curing agent described in any one of claims 1 to 7 and curing for 6 to 8 days; wherein the mass ratio of the gangue particles to the solid dry basis in the gangue heavy metal curing agent is (60 to 95): (40 to 5).

10. The method of use according to claim 9, characterized in that: The mass ratio of the gangue particles to the solid dry basis in the gangue heavy metal solidifying agent is (70-85): (30-15).

11. The method of use according to claim 9, characterized in that: The D50 of the gangue particles is 50-200 meshes.

12. The method of use according to claim 9, characterized in that: The gangue particles are formed by crushing gangue.

13. The method of use according to claim 12, characterized in that: The gangue is sintered at a high temperature of 600-900°C.

Citation Information

Patent Citations

  • Curing agent for treating heavy metal pollution and heavy metal curing method

    CN104418560A

  • Slurry for Treatment of Oxyanion Contamination in Water

    CN110862136A

  • Preparation method of argillized gangue curing agent

    CN112852073A